How we got here? Transition failures, their causes and the populist interest in the constitution. (December 2019) - Arato, Andrew
How is it possible, that after the exhilarating start of democratic transitions in the late 1980s and 1990s, today authoritarian–populist options seem to be emerging in many new, as well as old democracies? Why does populism, that in most of its historical varieties has been anti-institutional and anti-procedural, turn to constitution making and constitutional rhetorics as one of its main arenas of contestation? The answers to these questions are related. In the following, in the form of six theses, I start with what I mean by 'populism'. Next, I wish to point to the two deficits of liberal democracy that provides the context for the rise of populist politics. These deficits according to me have been intensified in many of the new democracies. I continue by stressing populisms own deficits as the reason for turning to the constituent power. I end with a consideration of what liberal democrats can do to address the causes of the populist temptation.